2005
DOI: 10.1524/zkri.2005.220.11_2005.973
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and crystal structure of a homotrinuclear Ni(II) complex

Abstract: A tetradentate ONNO type Schiff base was synthesized from salicyaldehyde and 1,4-diaminobutane. Thermogravimetric analysis, elemental analysis and X-ray diffraction results showed this Schiff base to give a trinuclear complex with Ni(II) ions in presence of acetate ions. The complex crystallizes in the triclinic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…There is a striking similarity between the salamo and salbn complexes, which have an –OCH 2 CH 2 O– and a –(CH 2 ) 4 – group, respectively, as a linker between the two sp 2 nitrogen atoms. The [M 3 L 2 ]‐type complexes were formed by the complexation of H 2 salamo and H 2 salbn with cobalt(II), nickel(II), and zinc(II) . This fact strongly indicates that the replacement of the methylene unit with one oxygen atom does not significantly change the structure of the complexes.…”
Section: Resultsmentioning
confidence: 99%
“…There is a striking similarity between the salamo and salbn complexes, which have an –OCH 2 CH 2 O– and a –(CH 2 ) 4 – group, respectively, as a linker between the two sp 2 nitrogen atoms. The [M 3 L 2 ]‐type complexes were formed by the complexation of H 2 salamo and H 2 salbn with cobalt(II), nickel(II), and zinc(II) . This fact strongly indicates that the replacement of the methylene unit with one oxygen atom does not significantly change the structure of the complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Transition metal complexes with salen-type or oxime-type ligands are extensively investigated, which have long been used as chelating ligands in the synthesis of transition metal complexes due to their ease of preparation and structural variety. These compounds play a seminal role in the development of modern coordination chemistry, which can accommodate several metal centers and form homo-and heteronuclear metal complexes with favourable properties 1 , such as their enormous variety of structural topologies, as well as their potential applications in optoelectronics, magnetism, non-linear optical materials 2 , biological activity 3 and catalysis [4][5][6][7][8] . To change the structures or improve the functions of the resulted complexes, herein, a new salamo-type bisoxime ligand, 2,2'-[(propylene-1,3-diyldioxy)bis(nitrilomethylidyne)]diphenol (H2L) and its transition metal complexes have been synthesized and structurally characterized.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, cyanoacetate ion was used as the bridging molecule [9][10][11]. The investigation of the thermal degradation of the title molecule revealed that the thermal dissociation of the molecule took place at much lower temperatures.…”
Section: Introductionmentioning
confidence: 99%